2019
DOI: 10.1021/acscatal.9b00330
|View full text |Cite
|
Sign up to set email alerts
|

Free Standing Nanoporous Palladium Alloys as CO Poisoning Tolerant Electrocatalysts for the Electrochemical Reduction of CO2 to Formate

Abstract: CO2 electrochemical reduction to formate has emerged as one of the promising routes for CO2 conversion to useful chemicals and renewable energy storage. Palladium has been shown to make formate with a high selectivity at minimal overpotential. However, production of CO as a minor product quickly deactivates the catalyst during extended electrolysis. Here, we present nanoporous Pd alloys (np-PdX) formed by electrochemical dealloying of Pd15X85 alloys (X = Co, Ni, Cu, and Ag) as active free standing electrocatal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
95
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(101 citation statements)
references
References 82 publications
6
95
0
Order By: Relevance
“…Although such a strategy has been applied as a general design principle of Pd alloys for electrocatalytic oxygen reduction reaction and alcohol oxidation reaction, [34][35][36][37] the alloying effect is much less explored and appreciated for CO 2 RR until very recently. [38][39][40][41] In this contribution, we investigate the great potential of 1D alloy nanowires of Pd and Ag in CO 2 RR electrocatalysis. Ag is selected as the second metal in the alloy for its electron-rich state and weak CO binding strength.…”
Section: Doi: 101002/adma202005821mentioning
confidence: 99%
“…Although such a strategy has been applied as a general design principle of Pd alloys for electrocatalytic oxygen reduction reaction and alcohol oxidation reaction, [34][35][36][37] the alloying effect is much less explored and appreciated for CO 2 RR until very recently. [38][39][40][41] In this contribution, we investigate the great potential of 1D alloy nanowires of Pd and Ag in CO 2 RR electrocatalysis. Ag is selected as the second metal in the alloy for its electron-rich state and weak CO binding strength.…”
Section: Doi: 101002/adma202005821mentioning
confidence: 99%
“…Pd-based alloys 68 at very low overpotential. Clearly, Figure 9 establishes a powerful thermodynamic selectivity map for CO2 reduction that not only rationalizes a large number of experimental observations but also offers a set of design principles that can help identify selective catalysts that target products such as formate, CO, and more reduced products like hydrocarbons or alcohols.…”
Section: Co* Forming Metals and Product Selectivitymentioning
confidence: 99%
“…Many studies have reported that the performance of the electrocatalytic CO2 reduction reaction (CO2RR) is compromised during electrolysis [2,[50][51][52]. This is often attributed to catalyst deactivation by the adsorption of reaction intermediates.…”
Section: Catalyst Poisoningmentioning
confidence: 99%
“…Thus, density-functional theory (DFT) calculations have often revealed higher binding energy between the poisoned catalysts and the implicated species. For instance, Pd metal is known to bind strongly to CO and is more likely to be poisoned and undergo activity degradation in a short duration of time due to the reduction of CO2 to CO [50][51][52]. The strong CO adsorption arises from an increase in 2π* back donation interaction (i.e., electron donation from the d orbitals of the metal substrate to the 2π* orbital of CO) as the formed bonding resonances are filled at a more negative potential [57].…”
Section: Catalyst Poisoningmentioning
confidence: 99%